El café y el desarrollo Histórico-Geográfico de Costa Rica: Vida y obra historiográfica de Carolyn Hall en perspectiva económica - Ramírez-Roldán, José David (2019)
When talking about historiographic renewal of the mid-70s, one would be remiss not to highlight British researcher Carolyn Hall’s work in the field of Costa Rican historical geography. This study surveys Carolyn Hall’s academic life and her contributions to methodology in the field of Costa Rican historiography history, paying special attention to her masterwork, El café y el desarrollo Histórico-Geográfico de Costa Rica. This research delves into an analysis of her theoretical influence to account for the economic aspect of her work.